India : 2009 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for India. (IMF Staff Country Reports; Country Report ;, 2010)
This 2009 Article IV Consultation highlights that India's medium-term growth prospects remain bright. Prompt fiscal and monetary easing, combined with the fiscal stimulus already in the pipeline and the return of risk appetite in financial markets, have brought growth close to pre-crisis levels. Risks to a favorable outlook stem primarily from difficulties in implementing productivity-enhancing reforms and continued supply bottlenecks. Executive Directors have congratulated the authorities on their strong record of sound macroeconomic policies and decisive actions leading to India's early and vigorous recovery from the global crisis.